Tapai - Natashah Md. Nor; Rusli Harun; Amelia Abd. Aziz (Malaysia : UAS Communications (M), 1997)
The making of tapai, Malaysian tradisional food especially in malay culture
Executive producer, Najib Shafion, Zabidi Sanip ; script, Amelia Abd. Aziz
Narrator: Reemy Abdul Rahman
Keywords: Food preservatives; Malays -- Food; Food -- Drying